Design and Anchorage Dependence of Shape Memory Alloy Actuators on Enhanced Voiding of a Bladder. Issue 1 (15th November 2017) - Hassani, Faezeh Arab; Gammad, Gil Gerald Lasam; Mogan, Roshini Priya; Ng, Tze Kiat; Kuo, Tricia Li Chuen; Ng, Lay Guat; Luu, Percy; Thakor, Nitish V.; Yen, Shih‐Cheng; Lee, Chengkuo
Abstract: The use of shape memory alloy (SMA) actuators to restore voiding of bladder for myogenic under active bladder (UAB) patients is proposed recently. Even though previous work show the unique capability of this technology for bladder voiding, the low voiding volume and high energy consumption of the device limit the advancement of this technique. This study proposes a novel approach using an interlaced configuration to overcome these limitations. In this device, SMA actuators are threaded through rigid anchor points of the flexible vest. The novel anchorage of SMA actuators provides more conformability for the vest and lower energy consumption for the device, while the new interlaced configuration enhances the voiding volume. The device is tested initially on a rubber model for the bladder, then it is implanted in an anesthetized rat, and a voiding volume of more than 20% at 4 V is successfully achieved. A commercial force sensor is integrated with the device to make it suitable for neurogenic UAB patients. The sensor provides a feedback control signal to the patient to initiate the actuation of the device upon fullness of bladder. The overall system is a promising advance over the state‐of‐the‐art providing bladder voiding in UAB patients. Abstract : A flexible device with a novel anchorage design and interlaced configuration for shape memory alloy actuators is proposed to enhance voiding of the bladder under reduced temperature and energy consumption by receiving a control signal from an integrated force sensor. The device is suitable for neurogenic underactive bladder patients who suffer from loss of bladder fullness sensing and detrusor muscle atrophy.